RADT-31. PATTERNS OF CARE IN THE USE OF ADJUVANT RADIOTHERAPY AND CHEMOTHERAPY IN LOW GRADE GLIOMA PATIENTS IN THE UNITED STATES FROM 2010-2016 - Rehrer, Warren (Neuro Oncol, 2020)
PURPOSE: In 2016, RTOG 9802 reported an overall survival advantage with the addition of chemotherapy to adjuvant radiotherapy (CRT) in patients with high-risk low grade glioma (LGG). We used the National Cancer Database (NCDB) to measure trends in CRT use in LGG patients from 2010-2016, a period when no Level 1 evidence existed. METHODS: The NCDB was queried for WHO Grade II glioma patients treated from 2010-2016 who met the inclusion criteria for RTOG 9802. Adjusted logistic regression was used to assess the association of treatment year with the annual percentage of patients who received adjuvant CRT. Relative percent change and average annual percentage change (AAPC) were compared to determine if a change (defined a priori as < 0.01) occurred in the use of adjuvant CRT in LGG patients during this period. RESULTS: The analytic cohort consisted of 5,039 patients; 64.3% of patients were 40 years or older and 35.7% were under 40 with subtotal resection. Use of adjuvant CRT increased from 18.9% to 49.7% (p< 0.001) during 2013-2016, with no change observed before 2013. The AAPC in the use of CRT was +39.6% per year (p< 0.001). Corresponding declines in patients treated with surgery alone (p< 0.001) and surgery plus radiotherapy (p< 0.001) were observed during 2013-2016. Logistic regression demonstrated patients who were under 40 years old were significantly less likely to receive adjuvant CRT than patients 40 years or older (Odds Ratio 0.561, 95% CI 0.475-0.663, p< 0.001). Use of adjuvant CRT increased from 12.5% to 45.1% in patients with oligodendroglioma during 2013-2016 (p< 0.001). CONCLUSIONS: During 2013-2016, an increasing number of patients with LGG were treated with surgery followed by adjuvant CRT. Future studies may characterize the use of single agent vs. multiagent chemotherapy in this population and the adoption of trimodality therapy by mutation status.